Attraction in buyer–supplier relationships: Improving supply network performance through purchasing recognition and proficient collaboration initiatives. Issue 2 (11th July 2018) - Patrucco, Andrea S.; Luzzini, Davide; Moretto, Antonella; Ronchi, Stefano
Abstract : Purpose: The purpose of this paper is to shed light on the dynamics of buyer–supplier industrial relationships and the role of customer attractiveness—a requisite to obtain best efforts from suppliers involved in collaborative initiatives. Design/methodology/approach: The paper develops a theoretical framework tested through an international survey with a structured equation modeling approach. Findings: Results confirm that customer attractiveness positively affects both innovation and cost performance ensured by suppliers. Moreover, several direct and indirect antecedents of customer attractiveness are identified, including characteristics of the buying firm's procurement department (i.e. procurement knowledge and procurement status) and supply chain relationship characteristics (i.e. proficiency of supplier collaboration and visibility). Research limitations/implications: Because of the survey approach, the research results are limited to the data collected. Practical implications: Findings support the relevance of collaborative relationships in improving performance, and the key role procurement department could play in managing the multifaceted aspects of supplier collaboration. Originality/value: This paper investigates, on the one hand, why customer attractiveness is relevant for supply chain management, and what are the effects on innovation and cost performance ensured by suppliers; on the other hand, antecedents of customer attractiveness are considered, with a main focus on organizational and relational procurement variables.